Protective effect of pancreatic β‐cells MIN6 by some medicinal plants in the Mekong Delta. Issue 5 (24th October 2018) - Bach, Le Thi; Dung, Le Tien; Tuan, Nguyen Trong; Phuong, Nguyen Thanh; Kestemont, Patrick; Quetin‐Leclercq, Joëlle; Hue, Bui Thi Buu
Abstract: Endoplasmic reticulum (ER) stress plays an important role in the pathogenesis of diabetes, contributing to pancreatic β ‐cell loss and insulin resistance in type 2 diabetes mellitus (T2DM). In this study, the effect of ethanol extracts of Euphorbia hirta L. (Eup), Phyllanthus amarus L. (Phy), Mimosa pudica L. (Mim), Psidium guajava L. (Psi) and Azadirachta indica A. Juss (Aza) collected in the Mekong Delta on ER stress‐induced apoptosis in mouse β ‐cell lines was investigated. The results showed that, among tested extracts, Aza and Eup extracts gave the strongest cell‐protective effect improving cell viability to 76 % and 69 % at the dose of 0.1 mg/mL, respectively. These results indicated that Aza and Eup possess the potential to be developed as novel drugs against T2DM.